Pengaruh Kerjasama Tim dan Komunikasi terhadap Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Kerinci dengan Disiplin Kerja sebagai Variabel Intervening - Devia Adriani; Suhelmi Helia (Fakultas Syariah IAIN Kerinci, 2025)
This study examines the effects of teamwork and communication on employee performance with work discipline as an intervening variable at the Kerinci Regency Education Office. An associative quantitative approach was applied using a census method involving 45 civil servants. Data were collected through Likert-scale questionnaires and analyzed using path analysis with SPSS. The findings indicate that teamwork, communication, and work discipline have positive and significant effects on employee performance. Teamwork and communication also significantly influence work discipline. Furthermore, work discipline mediates the relationship between teamwork, communication, and performance. The model explains 50,8% of the variance in employee performance. These results emphasize the strategic role of collaboration, effective organizational communication, and work discipline in enhancing public sector performance.